2020
DOI: 10.3934/mbe.2020240
|View full text |Cite
|
Sign up to set email alerts
|

Research of the work of the sieve mill of a grain-cleaning machine with a linear asynchronous drive

Abstract: <abstract> <p>This article presents the results of a study of the sieve mill of a grain cleaning machine with a drive based on a linear asynchronous motor instead of a classic mechanical drive. The purpose of this work is to describe the structural and technological parameters of a sieve mill with a linear asynchronous drive to implement a mathematical model of the technological process of a grain cleaning machine work. A kinematic study of the flat hinged mechanism of the sieve mill of a grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The first scheme represents a sequentially installed separation screen B1 and a feeder screen B2 in the upper tier, and two cleaning screens C in the lower tier, the dimensions of the holes of which are equal to B1 = 3.0 mm; B2 = 3.6 mm, C = 2.0 mm. This scheme makes it possible to extract only large and small impurities from grain, so it can only be used for preliminary or primary cleaning [9][10][11][12][13]. coarse impurities; main fraction; 1frame; 2tray for large impurities; 3tray for the main fraction; 4forage tray; 5tray for fine impurities; 6slide surface In the second studied scheme of screen arrangement, a sorting screen D and a feeder screen B2 are sequentially installed in the upper tier, and in the lower tierthe cleaning screen C and the sorting screen D are installed, the sizes of holes of which are equal to B2 = 3.6 mm, D = 2.6 mm, C = 2.0 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The first scheme represents a sequentially installed separation screen B1 and a feeder screen B2 in the upper tier, and two cleaning screens C in the lower tier, the dimensions of the holes of which are equal to B1 = 3.0 mm; B2 = 3.6 mm, C = 2.0 mm. This scheme makes it possible to extract only large and small impurities from grain, so it can only be used for preliminary or primary cleaning [9][10][11][12][13]. coarse impurities; main fraction; 1frame; 2tray for large impurities; 3tray for the main fraction; 4forage tray; 5tray for fine impurities; 6slide surface In the second studied scheme of screen arrangement, a sorting screen D and a feeder screen B2 are sequentially installed in the upper tier, and in the lower tierthe cleaning screen C and the sorting screen D are installed, the sizes of holes of which are equal to B2 = 3.6 mm, D = 2.6 mm, C = 2.0 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The linear electric motors used as the actuators of vibrating machines can easily change all the above-mentioned technological parameters by the signals from accelerometers, realizing efficient feedback loop control. Aipov et al [73] developed a sieve mill for a grain cleaning machine driven by a linear induction motor. It is shown that the advantage of a linear induction motor compared to standard drive designs is significantly less metal consumption for drive shafts, transmission elements, connecting shafts, bearings, and structure.…”
Section: Sieving Screensmentioning
confidence: 99%
“…Since further development is impossible when using the classical scheme of sieve drives, in work of Aipov et al [19], it is proposed to use two rotational vibrators with the same or different static moments. The sieve (screen) trajectory is characterized by two different rotation speeds of the drive eccentric-type vibrators.…”
Section: Introductionmentioning
confidence: 99%